Role of Panchakarma in the Management of Avascular Necrosis of Femoral Head (AYUSHDHARA, 2025)
Avascular Necrosis of the Femoral Head (AVNFH) is a degenerative bone disorder that progressively impairs joint function and mobility, often affecting young and middle-aged adults. The condition arises from disrupted blood supply to the femoral head, leading to bone tissue death and, in advanced stages, joint collapse. This poses significant challenges for long-term management, particularly in younger patients, where surgical interventions such as total hip replacement may not be ideal. This case study presents the Ayurvedic management of a 37-year-old female diagnosed with Grade 4 AVNFH of the left femoral head. Despite prior allopathic treatment yielding limited relief, the patient showed marked clinical improvement following a comprehensive Panchakarma-based approach including Sarvanga Abhyanga, Mahamanjishtadi Kashaya Seka, Manjishtadi Kshara and Kashaya Basti, Panchatikta Ksheera Basti, Anuvasana Basti with Guggulu Tiktaka Ghrita, and Navara Dhara. These therapies targeted Srotoshodhana, Asthi Dhatu Poshana, and functional restoration. Significant improvements were observed in pain (VAS reduced from 9 to 3), range of motion, gait, and the Harris Hip Score (from 35.5 to 66.35). The results highlight the potential of Ayurvedic interventions, particularly Panchakarma, in managing advanced stages of AVNFH, potentially delaying or avoiding surgical interventions such as total hip replacement.